STUDY ON HEAT TRANSFER PERFORMANCE OF PLATE-FIN RADIATOR BASED ON COMPUTATIONAL FLUID DYNAMICS - ZHANG Min; GAO Chan (Jixie qiangdu)
In order to enhance heat transfer performance of plate-fin radiator,multi-objective optimization was carried out to the structural parameters of the serrated fin based on the genetic algorithm. According to the result of optimization,threedimensional physical model of the channel was built. The temperature field was investigated by the method of CFD. The heat transfer factor,friction factor and comprehensive performance evaluation factor of fin were obtained. The simulation results show that the heat transfer performance of the optimized fin was improved. Heat transfer performance of copper fin is better than that of aluminum fin. The validity of the simulation result is verified by wind tunnel test.